Sex-specific interaction effects of age, occupational status, and workplace stress on psychiatric symptoms and allostatic load among healthy Montreal workers. (November 2013) - Juster, Robert-Paul; Moskowitz, D. S.; Lavoie, Joel; D'Antono, Bianca
Abstract Socio-demographics and workplace stress may affect men and women differently. The aim of this cross-sectional study was to assess sex-specific interactions among age, occupational status, and workplace Demand-Control-Support (D-C-S) factors in relation to psychiatric symptoms and allostatic load levels representing multi-systemic "wear and tear". It was hypothesized that beyond main effects, D-C-S factors would be moderated by occupational status and age in sex-specific directions predictive of subjective psychiatric symptoms and objective physiological dysregulations. Participants included healthy male (n = 81) and female (n = 118) Montreal workers aged 20 to 64 years (Men: M = 39.4 years, SD = 11.3; Women: M = 42.8 years, SD = 11.38). The Job Content Questionnaire was administered to assess workplace D-C-S factors that included psychological demands, decisional latitude, and social support. Occupational status was coded using the Nam--Powers--Boyd system derived from the Canadian census. Psychiatric symptoms were assessed using the Beck Anxiety Scale and the Beck Depression Inventory II. Sex-specific allostatic load indices were calculated based on fifteen biomarkers. Regression analyses revealed that higher social support was associated with less depressive symptoms in middle aged (p = 0.033) and older men (p = 0.027). Higher occupational status was associated with higher allostatic load levels for men (p = 0.035), while the reverse occurred for women (p = 0.048). Women with lower occupational status but with higher decision latitude had lower allostatic load levels, as did middle-aged (p = 0.031) and older women (p = 0.003) with higher psychological demands. In summary, age and occupational status moderated workplace stress in sex-specific ways that have occupational health implications.